2017
DOI: 10.1016/j.celrep.2017.07.076
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Encodes Retrospective Temporal Information in a Context-Independent Manner

Abstract: Summary The dopamine system responds to reward-predictive cues to reflect a prospective estimation of reward value, though its role in encoding retrospective reward-related information is unclear. We report cue-evoked dopamine release in the nucleus accumbens core encodes the time elapsed since the previous reward, or rather the wait time. Specifically, a cue that always follows the preceding reward with a short wait time elicits a greater dopamine response relative to a distinct cue that always follows the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(101 citation statements)
references
References 30 publications
5
95
1
Order By: Relevance
“…We identified both increases and decreases in VMS dopamine levels that occurred during distinct periods of the aversive event, which suggests the discrepancies between earlier microdialysis studies likely arise from differences in the experimental parameters of the aversive task. We previously found that the engagement of the dopamine system during reward-based Pavlovian conditioning can be influenced by changes in the training context (35). Therefore, the training procedures, aversive cue duration, intensity and frequency of the footshock, presence of safety cues, and location of the recordings in the ventral striatum are all factors that likely contribute to the dopamine signals observed during aversive tasks (11,25,(31)(32)(33)(34)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified both increases and decreases in VMS dopamine levels that occurred during distinct periods of the aversive event, which suggests the discrepancies between earlier microdialysis studies likely arise from differences in the experimental parameters of the aversive task. We previously found that the engagement of the dopamine system during reward-based Pavlovian conditioning can be influenced by changes in the training context (35). Therefore, the training procedures, aversive cue duration, intensity and frequency of the footshock, presence of safety cues, and location of the recordings in the ventral striatum are all factors that likely contribute to the dopamine signals observed during aversive tasks (11,25,(31)(32)(33)(34)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Voltammetry Recordings. Chronically implanted carbon-fiber microelectrodes were connected to a head-mounted voltammetric amplifier for dopamine detection in behaving rats using fast-scan cyclic voltammetry as described previously (35,45). The potential applied to the carbon fiber was ramped in a triangular waveform from −0.4 V (vs. Ag/AgCl) to +1.3 V and back at a rate of 400 V/s during a voltammetric scan and held at −0.4 V between scans at a frequency of 10 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…During interval timing, the need for cognitive control is triggered by the cue, which initiates temporal processing (Buhusi and Meck 2005;Meck et al 2008). In fixed-interval timing tasks, the cue functions as a reward-predictive CS+ involving phasic dopamine release from midbrain dopamine neurons (Schultz 1997;Fonzi et al 2017). D1DR neurons respond to this phasic dopaminergic release early in the interval and initiate temporal processing via delta-range coherence with MFC ramping neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this view, direct activation of DA neurons serves as a potent reinforcer of instrumental behavior in self-stimulation procedures [7, 1822]. More recently, contributions of phasic DA signals to model-based learning have been suggested, based on evidence that DA neurons have access to higher-order knowledge for RPE computation [2327]. Moreover, DA neurons were shown to respond to valueless changes in sensory features of expected rewards [28], and DA neuron optogenetic inhibition prevented learning induced by changing either reward identity or value [29].…”
Section: Introductionmentioning
confidence: 99%